Denture of patients with diabetes (review) - T. P. Теrеshinа; T. I. Dimcheva; P. V. Маksimenko; O. V. Кіrіchеk (Kazimierz Wielki University, 2017)
In article results of the state-of-the-art review of literature are provided. It is shown that dental orthopedic rehabilitation of patients with diabetes is considerable difficulties because of a number of pathological manifestations in an oral cavity. It is indicated the need of holding preventive actions before prosthetics. And the choice of the correct structural materials and a design of an artificial limb providing optimum load distribution on fabric of the periodontium, adaptation of occlusal relationship and not irritating mucous a mouth